Building resilience through cooperation: Two case studies. Issue 1 (18th January 2021) - Brown, Josh; Jones, Phill; Meadows, Alice; Murphy, Fiona
Key points: There is evidence that cooperatives provide greater resilience in times of crisis than conventional enterprises. Cooperatives subscribe to seven values associated with economic and governance participation, as well as equality and concern for community. We present two case studies, one well established (Crossref) and one new (the UK National Research Identifier Coordinating Committee), that have adopted some cooperative principles. There is a strong push towards greater cooperation in the scholarly communications sector. There is enough evidence from our own sector and the wider socio‐economic landscape to justify prioritizing cooperation and cooperative values in our common endeavours in coming years.